A Comparison of Pain Scale on Neonates in a Top Refferal Hospital in Indonesia - Septiana, Nenty; Rustina, Yeni; Efendi, Defi (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Pain assessment scale in neonates is the cornerstones of pain management so that the impact of pain can be prevented to maximize neonatal growth and development.Purpose: This study aimed to identify the most appropriate pain assessment scale used for neonates in Indonesia.Methods: A cross sectional study design was used in 30 neonates hospitalized using Neonatal Infant Pain Scale (NIPS), Neonatal infant Acute Pain Assessment Scale (NIAPAS) and Pain Assessment Tool (PAT). Pain assessment was performed by nurses (n=30) and expert nurses (n=5) participated in the validation of scales. Statistical analysis using validity (content, construct and concurrent validity) and reliability (inter-rater reliability and internal consistency) test.Results: NIPS instrument have excellent validity, reliability, and feasibility value compared with NIAPAS and PAT.Conclusion: NIPS was shown a valid, reliable, and practical scale for assessing pain in neonates. It allows nurses to identifying pain and help to provide of appropriate pain management